Torque-Vectoring-Based Backup Steering Strategy for Steer-by-Wire Autonomous Vehicles With Vehicle Stability Control - Kirli, Ahmet; Chen, Yusen; Okwudire, Chinedum E.; Ulsoy, Ali Galip (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
Steer-by-wire (SBW) systems provide significant benefits to classical vehicles, and are indispensable for fully autonomous vehicles (AVs). A backup (emergency) strategy is needed to steer an AV equipped with SBW to safety if its steering actuator fails completely. Differential drive assisted steering (DDAS), which uses torque vectoring(TV) to steer a vehicle in the absence of a steering actuator, has been proposed as a backup strategy for SBW systems. However, vehicle stability control (VSC) - a required feature in most modern vehicles-also relies on TV to assist vehicles in maintaining stability. In this paper, it is shown through stability analyses on a linearized vehicle model that VSC enhances the stability of an AV equipped with a fully functional SBW system. Conversely, when combined with DDAS as a backup steering strategy for a failed SBW system, VSC typically deteriorates stability. Thus, the benefits of VSC in ensuring stability cannot be taken for granted for AVs, e.g., by designing it as a decoupled controller added on to DDAS. Instead, VSC and DDAS must be designed in an integrated manner to guarantee stability. To support this finding, simulations are conducted where a nonlinear AV model with either SBW or DDAS - both combined with VSC and implemented via model predictive control-are used to carry out an ISO - standard double lane change test at 80 km/h. Using the SBW system, the AV passes the test, both with VSC decoupled from and integrated with the SBW system. However, in the case of SBW failure, the AV with VSC decoupled from DDAS fails the test, while that with VSC integrated with DDAS completes the test successfully.
Keywords: Autonomous vehicles; optimal control; stability; steering systems; vehicle safety; Engineering; Telecommunications; Transportation